ID Systems and SOGI Inclusive Design - Lebbos, Toni Joe; Esquivel-Korsiak, Victoria; Clark, Julia (World Bank, Washington, DC, 2021)
The Principles on Identification for Sustainable Development, endorsed by 30 organizations, provides a framework for how to design identification (ID) systems that fulfill the promise of inclusive, sustainable development. The first principle on inclusion seeks to ensure universal access to identification, free from discrimination. To realize this ideal in practice, ID systems need to be fully inclusive of and accessible to all individuals regardless of their sexual orientation or gender identity (SOGI). This note describes key issues and emergent good practices to help practitioners build inclusive ID systems that prevent or reduce discrimination against individuals based on SOGI.